2014
DOI: 10.2166/wp.2014.121
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of farm-level adaptation diversity to cyclone and flood: insights from a farm household-level survey in Eastern India

Abstract: A large number of farmers' livelihoods are susceptible to cyclones and floods, and farmers are taking up several adaptation mechanisms. Previous studies, therefore, have examined determinants of various adaptation options and provide policy suggestions to promote a specific one. However, options are undertaken at different points depending on the nature and intensity of extreme events. Hence, it is imperative to identify factors influencing farmers' decisions to adopt an additional option, particularly during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…As discussed in the preceding section, the state economy is agrarian, and previous studies also report that agricultural output is more likely to be affected by cyclones and floods (Bhattacharya and Das 2007;Rao 2010). Further, Bahinipati (2014) also find that indicators related to agriculture emerged as the major determinants of vulnerability in Odisha. For instance, an average of 0.33 million ha agricultural land was damaged in the state due to flood during 1953-2011, which converts into a financial loss of INR 0.32 billion per year (GoO 2013).…”
Section: Methodsmentioning
confidence: 72%
See 4 more Smart Citations
“…As discussed in the preceding section, the state economy is agrarian, and previous studies also report that agricultural output is more likely to be affected by cyclones and floods (Bhattacharya and Das 2007;Rao 2010). Further, Bahinipati (2014) also find that indicators related to agriculture emerged as the major determinants of vulnerability in Odisha. For instance, an average of 0.33 million ha agricultural land was damaged in the state due to flood during 1953-2011, which converts into a financial loss of INR 0.32 billion per year (GoO 2013).…”
Section: Methodsmentioning
confidence: 72%
“…The district with higher value for these exposure indicators is expected to be more vulnerable. It is observed that the coastal districts of Odisha are experience a relatively higher number of cyclones and floods (GoO 2011), and in particular, the intensity of cyclones is likely to be high for these districts (Bahinipati 2014)-therefore, the households living in the coastal districts are more exposed to these events. As discussed in the preceding section, the state economy is agrarian, and previous studies also report that agricultural output is more likely to be affected by cyclones and floods (Bhattacharya and Das 2007;Rao 2010).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations